Social glocalisation and education : social work, health sciences, and practical theology perspectives on change. (BARBARA BUDRICH, 2020)
This book discusses the local effects of globalisation, especially in the context of social work, health and practical theology, as well as the challenges of higher education in a troubled world. The more globalised the world becomes, the more important local identities are. The global becomes effective in the local sphere. This phenomenon, called 'glocalisation' since the 1990s, poses many challenges to people and to the social structures in which they operate.